Nutrition Knowledge among College of Basic Education Students in Kuwait: A Cross-Sectional Study - Wafaa Husain; Fatemah Ashkanani; Maryam A. Al Dwairji (Journal of Nutrition and Metabolism)
Lack of nutrition knowledge may contribute to poor dietary practices. Schools are an ideal environment to address this issue and to start the process of nutrition education. Therefore, teachers should be equipped with adequate nutrition knowledge. This study was designed to evaluate the level of general nutrition knowledge and demographic variations in knowledge in a sample of students attending the College of Basic Education in Kuwait. A cross-sectional study was conducted using a modified and validated revised version of the General Nutrition Knowledge Questionnaire (GNKQ-R) for UK adults. Univariate and multivariate analyses were performed to determine the association between various factors and nutrition knowledge score. A total of five hundred and ninety-seven students completed the questionnaire. Most respondents (84.1%) had a poor level of nutrition knowledge using original Bloom’s cutoff points. Sex, BMI, cooking habits, and who is responsible for preparing food in the household were the main determinants of nutrition knowledge score at p < 0.05. The mean score of the students was 40.06 ± 9.89 out of 84 points. Females scored significantly higher than males, at 41.10 ± 9.29 and 38.72 ± 10.48, respectively (p = 0.007). Students with a BMI of ≥30 achieved significantly greater scores (mean 42.30 ± 9.41) than those who were underweight, normal, or overweight (p < 0.001). Students who stated that they always cook their own food achieved significantly greater scores (mean 43.69 ± 9.58) than those who did not (p = 0.025). Students who stated that they depend on the housekeeper for food preparation achieved significantly lower scores (mean 38.86 ± 10.13) than those who prepare their own food or depend on their relatives to prepare food (p = 0.042). Poor nutrition knowledge was found among prospective teachers studying in the College of Basic Education. This must be rectified for the effective implementation of nutrition education programs in schools.